The Adoption of QR Code Mobile Payment Technology During COVID-19: A Social Learning Perspective - Tu, Ming; Wu, Lei; Wan, Hua; Ding, Zhoujin; Guo, Zizheng; Chen, Jiayi (Frontiers in Psychology, 2022)
The increasing number of QR code mobile payment users heralds the coming of a cashless society. However, the extent to which the COVID-19 pandemic accelerated the adoption of QR code mobile payment has been insufficiently researched. Based on social learning theory, this paper models how external interaction with the environment affected the internal appraisal and behavioral intention to adopt QR code mobile payment during COVID-19. Empirical results from 248 respondents reveal that perceived severity and social influence positively affect respondents’ perception of utilitarian and health benefits, which in turn influences the behavioral intention to use QR code mobile payment. The theoretical contribution and managerial implications of this study are also discussed.